Modification of a cement binder in structural concrete for mine and underground construction - Uglyanitsa Andrey (EDP Sciences, 2021)
The issues of the modification of a binder in structural cement concrete for mine and underground construction with wastes of chemical enterprises are considered in the article. Hundreds of tons of waste are generated annually at chemical enterprises of the Russian Federation, polluting the environment and requiring their disposal. The performed studies deal with the improvement of physical and mechanical properties of a cement binder with a dispersed manganese sludge modifier, which is a waste product of ammonia or methanol production, for its use in mine and underground construction. As a result of the studies performed, it was found that the addition of dispersed sludge with manganese oxide in an amount of 4% of the cement mass to a cement binder leads to the activation of the cement hydration process, while the rate of development of the plastic strength of the cement stone structure increases, the period of its structure formation reduces and the compressive cement stone strength increases by 17-18%, which makes it possible to reduce the cement content in structural concrete by 8.8-10.0% while maintaining its strength, reducing the cost of mine and underground structures and, as a result, reducing the cost of mining.